CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE: AN ANALYSIS UNDER THE PRISM OF RECIPROCITY - TIONA WAMBA JOSEPH HERMAN (Université Mohammed V de Rabat, 2020)
This paper lays the foundations of the mutual contribution of CSR and corporate financial performance. It seeks to find out whether CSR can explain and be explained by corporate financial performance. We introduce moderating and mediating variables to throw light on the reciprocal relationship envisaged. We combine qualitative and quantitative methodological approaches to verify our research hypotheses. The main result talks of a non-reciprocalbut ambiguous cyclical relationship between CSR and FP. We thusconclude on the possibility to study this link by replacing CSR by Socially Responsible Investment (SRI)